QTc Dynamics Following Cardioversion for Persistent Atrial Fibrillation - Younis, Arwa; Nehoray, Nofrat; Glikson, Michael; Bodurian, Christopher; Nof, Eyal; Bragazzi, Nicola Luigi; Berger, Michael; Zareba, Wojciech; Goldenberg, Ilan; Beinart, Roy (Frontiers in Cardiovascular Medicine, 2022)
Background– Cardioversion (CV) for atrial fibrillation (AF) is common. We aimed to assess changes in QTc over time following electrical CV (ECV) for persistent AF, and to compare the benefit of using continuous Holter monitoring vs. conventional follow-up by ECG. Methods– Prospective observational cohort study. We comprised 90 patients admitted to our center for elective ECV due to persistent AF who were prospectively enrolled from July 2017 through August 2018. All patients underwent 7-day Holter started prior to ECV. Baseline QTc was defined as median QTc during first hour post ECV. The primary endpoint was QTc prolongation defined as QTc ≥500ms, or ≥10% increase (if baseline QTc was >480ms). Conventional monitoring was defined as 2-hours ECG post ECV. Results- Mean age was 67 ± 11 years and 61% were male. Median baseline QTc was 452msec (IQ range: 431-479msec) as compared with a maximal median QTc of 474msec (IQ range: 433–527msec; p<0.001 for the change in QTc from baseline). Peak median QTc occurred 44 hours post ECV. The primary endpoint was met in 3 patients (3%) using conventional monitoring, compared with 39 new patients (43%) using Holter (p<0.001 for comparison). The Holter monitoring was superior to conventional monitoring in detecting clinically significant QTc prolongation (OR=13; p<0.001). Conclusions– ECV of patients with persistent AF was associated with increased transient risk of QTc prolongation in nearly half of the patients. Peak median QTc occurs during end of second day following ECV and prolonged ECG monitoring provides superior detection of significant QTc prolongation compared with conventional monitoring.